Ontology-Based Semantic Search on Tourism Information Search System - Ranestari Sastriani; Z K Abdurahman Baizal; Dana Sulistyo Kusumo (School of Computing, Telkom University, 2020)
Nowadays, search engines are used to find various information on the Web. Search engines that are implied traditional search based on keywords do not always provide relevant information. Meanwhile by semantic search can provide relevant results because it can understand the meaning of the context and its connection. One approach to semantic search is to use ontology. Ontology is used to define concepts and relevant relations in a domain. In Information Retrieval (IR), an ontology encompasses in returning relevant information from a collection of unstructured information. One application of ontology in IR is query expansion. In this research, The query entered by the users will be searched for its relation to the ontology domain which will be expanded later. We use tourism in Bandung Raya as an ontology domain. The search in this research is represented by using Vector Space Model (VSM). Furthermore, relevant documents from search result will be provided to users. Based on the results of testing, the system that is built is able to provide relevant information with an average MAP value better than the search system that only uses traditional search methods.